Energy transduction and signal averaging of fluctuating electric fields by a single protein ion channel. Issue 1 (30th November 2016) - Verdia-Baguena, C.; Gomez, V.; Cervera, J.; Ramirez, P.; Mafe, S.
Abstract : A biological ion channel is used to charge a conventional capacitor from an external fluctuating electrical noise. Abstract : We demonstrate the electrical rectification and signal averaging of fluctuating signals using a biological nanostructure in aqueous solution: a single protein ion channel inserted in the lipid bilayer characteristic of cell membranes. The conversion of oscillating, zero time-average potentials into directional currents permits charging of a load capacitor to significant steady-state voltages within a few minutes in the case of the outer membrane porin F (OmpF) protein, a bacterial channel of Escherichia coli . The experiments and simulations show signal averaging effects at a more fundamental level than the traditional cell and tissue scales, which are characterized by ensembles of many ion channels operating simultaneously. The results also suggest signal transduction schemes with bio-electronic interfaces and ionic circuits where soft matter nanodiodes can be coupled to conventional electronic elements.